RECURRENT HYPOGLYCAEMIA IN A PATIENT WITH TOTAL GASTRECTOMY - Ho, Cheuk Wah (Journal of the ASEAN Federation of Endocrine Societies, 2022)
CASE A 56-year-old male hostel resident with a past history of spastic diplegic cerebral palsy was repeatedly admitted for hypoglycaemia since January 2021. Past medical history revealed that on August 2018 he had a 5 cm bleeding acute gastroduodenal ulcer which required total gastrectomy and duodenostomy. He had several admissions for severe symptomatic hypoglycaemia in 2021 (January, February, May, June, July). He denied history of over- the-counter medication or alcohol intake. He experienced hypoglycaemia after meals. Prolonged 75 g oral glucose tolerance test showed hypoglycaemia at 3 hours with a glucose level of 1.7 mmol/l and paired insulin of 4.3 mIU/l. Thyroid function test and 1 μg short synacthen test results were normal. Urine toxicology was normal. He was referred to a dietitian on September 2021 and was given a trial of 2 tablespoons uncooked cornstarch (UCS) with water. He did not have any hospital admissions for hypoglycaemia since then. The home sugar monitoring showed capillary glucose mostly at 4-5 mmol/l, occasionally down to 2.9 mmol/l but not requiring admission. The patient suffered from late dumping syndrome which is also seen in post-bariatric surgery patients. After sleeve gastrectomy or bypass surgery, as the undigested food has rapid transit to the small intestine, it stimulates release of gut hormones including glucagon-like-peptide 1 which causes hypoglycaemia. Dietary modification includes small frequent meals and increasing dietary fibre intake. The UCS has a low glycaemic index. It slows down the absorption of glucose and rise in blood glucose. If the patient fails dietary measure, acarbose, diaxozide and somatostatin analogue are the next steps. If the patient fails medical treatment, he may need surgical re-intervention such as pyloric reconstruction.